2015
DOI: 10.1158/2159-8290.cd-15-0892
|View full text |Cite
|
Sign up to set email alerts
|

Infection Exposure Is a Causal Factor in B-cell Precursor Acute Lymphoblastic Leukemia as a Result ofPax5-Inherited Susceptibility

Abstract: Earlier in the past century, infections were regarded as the most likely cause of childhood B-cell precursor acute lymphoblastic leukemia (pB-ALL). However, there is a lack of relevant biologic evidence supporting this hypothesis. We present in vivo genetic evidence mechanistically connecting inherited susceptibility to pB-ALL and postnatal infections by showing that pB-ALL was initiated in Pax5 heterozygous mice only when they were exposed to common pathogens. Strikingly, these murine pB-ALLs closely resemble… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
189
1
7

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 130 publications
(231 citation statements)
references
References 50 publications
12
189
1
7
Order By: Relevance
“…However, we did not find this high proportion of differentially regulated epigenetic regulator genes in a related Pax5 þ/À model of pB-ALL (Table 2 and Supplementary Table S5; ref. 46). These data indicate that ETV6-RUNX1 specifically regulates transcription of histone modifying genes of the KDM family and support a specific role of histone modification in preleukemic ETV6-RUNX1 cells (Supplementary Table S5).…”
Section: Long-term Hematopoietic Stem Cells (Lt-hsc) Short-term Hemasupporting
confidence: 67%
See 1 more Smart Citation
“…However, we did not find this high proportion of differentially regulated epigenetic regulator genes in a related Pax5 þ/À model of pB-ALL (Table 2 and Supplementary Table S5; ref. 46). These data indicate that ETV6-RUNX1 specifically regulates transcription of histone modifying genes of the KDM family and support a specific role of histone modification in preleukemic ETV6-RUNX1 cells (Supplementary Table S5).…”
Section: Long-term Hematopoietic Stem Cells (Lt-hsc) Short-term Hemasupporting
confidence: 67%
“…We previously proved the infectious hypothesis stated by Ward in 1917 in a murine model of Pax5 haploinsufficiency (46), which can now be extended to the commonest subtype of childhood leukemia. It is of much broader interest for our general understanding of leukemia development to know if the very common ETV6-RUNX1 fusion acts cooperatively with infection.…”
Section: Discussionmentioning
confidence: 57%
“…One example of this latter category could be PAX5 mutations. Based on murine models, PAX5 impairment may not significantly affect hematopoietic differentiation, but in cooperation with immune stimuli may facilitate acute B-cell transformation [124]. Finally, it remains to be determined whether mutations would be specific for the third step.…”
Section: Discussionmentioning
confidence: 99%
“…PAX5 locks B-cell differentiation as PAX5-deficient cells are able to trans-differentiate in T and myeloid cells [122,123]. Furthermore Pax5 heterozygous mice show an accumulation of IL7-dependant proB cells and develop B-ALL when challenged by infections [124]. Translocations and mutations involving PAX5 have been observed in B-cell lymphomas [125] and B-ALL [126].…”
Section: Noncoding Mutations Affecting Pax5 Transcriptional Regulationmentioning
confidence: 99%
“…Experimental studies in mice have shown that PAX5 mutation, a predisposing risk factor in some childhood ALL cases, can result in development of ALL following exposure to common infection. 17 Though there is no apparent relationship between the germline APOBEC3B deletion polymorphism and ALL risk, delineating a potential role for the polymorphism in tumor progression may have treatment implications, warranting further study.…”
mentioning
confidence: 99%